If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5m + -10)(m + 4) = 0 Reorder the terms: (-10 + 5m)(m + 4) = 0 Reorder the terms: (-10 + 5m)(4 + m) = 0 Multiply (-10 + 5m) * (4 + m) (-10(4 + m) + 5m * (4 + m)) = 0 ((4 * -10 + m * -10) + 5m * (4 + m)) = 0 ((-40 + -10m) + 5m * (4 + m)) = 0 (-40 + -10m + (4 * 5m + m * 5m)) = 0 (-40 + -10m + (20m + 5m2)) = 0 Combine like terms: -10m + 20m = 10m (-40 + 10m + 5m2) = 0 Solving -40 + 10m + 5m2 = 0 Solving for variable 'm'. Factor out the Greatest Common Factor (GCF), '5'. 5(-8 + 2m + m2) = 0 Factor a trinomial. 5((-4 + -1m)(2 + -1m)) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(-4 + -1m)' equal to zero and attempt to solve: Simplifying -4 + -1m = 0 Solving -4 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1m = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1m = 0 + 4 -1m = 0 + 4 Combine like terms: 0 + 4 = 4 -1m = 4 Divide each side by '-1'. m = -4 Simplifying m = -4Subproblem 2
Set the factor '(2 + -1m)' equal to zero and attempt to solve: Simplifying 2 + -1m = 0 Solving 2 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1m = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1m = 0 + -2 -1m = 0 + -2 Combine like terms: 0 + -2 = -2 -1m = -2 Divide each side by '-1'. m = 2 Simplifying m = 2Solution
m = {-4, 2}
| -6=2x+2(x+3) | | c(200)=6.2x+10100 | | 15+12/2= | | X+8=76 | | -10n+4=-86 | | (5+7i)(4-12i)= | | -11x+12=-7x | | 86900=-19.2+2.4x | | y+7=8(x-1) | | 9+3x+12=8x-9-5x | | 7y+6(y-4)=2 | | c(200)=6.2+10100 | | 3x-2(8-2x)=5 | | 2x=2+-14 | | X-0.75=1.00 | | 6=2(y-7)-7y | | 3-5k=88 | | 6+-x=1 | | h-25=2h-8 | | m-1=96 | | 8(-8x-6)=6x-22 | | 2n+n-6=30 | | -4=(v+1) | | -34=8u+2(u+7) | | 1.9(1.6+3.7)= | | 2(x*7)=5(x-7) | | 5(z-1)=(4z+4) | | (x-3)=(6x-2) | | X+11x-2=0 | | 2(x-2)+14=10x+5-4x | | 36x^2+25=60 | | 7=(-5v-8) |